KOMUNITAS SERANGGA PADA BUNGA RAFFLESIA PATMA BLUME (RAFFLESIACEAE) DI LUAR HABITAT ASLINYA KEBUN RAYA BOGOR KOTA BOGOR PROVINSI JAWA BARAT INDONESIA - Kahono, Sih; Mursidawati, Sofi; Erniwati, Erniwati (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTInsects Community on the Flower of Rafflesia patma Blume (Rafflesiaceae) in its Non NativeHabitat of Bogor Botanical Gardens, Bogor City, Province of West Java, Indonesia. The studywas conducted at the Bogor Botanical Gardens, Bogor, West Java, Indonesia using a bloomingfemale flower of R. patma. The insects were directly counted in the morning, noon, and afternoonon both fresh blooming and rotten R. patma . Twenty three insect species were collectedduring the study belonging to the order Coleoptera (2 families, 2 species, 5 individuals),Diptera (9 families, 18 species, 1176 individuals), and Hymenoptera (2 family, 4 species, 13individuals). Number of individuals of each insect species captured were frequently less than1.35% from total captured. There were specialization of flies visiting fresh opening flower andthe rotten one. Six species, Leiomyza laevigata (Asteiidae), Chrysomya megacephala, andHemipyrellia tagaliana (Calliphoridae), Stegana coleoptrata (Drosophilidae), Heteromyzaoculata and Tephrochlamys rufiventris (Heleomyzidae) were predicted as important pollinatorsof R. patma.Key words: Insect community, flower, Rafflesia patma, non native habitat, Bogor BotanicGarden.